# Solve for z 9(z-1)=-3(3-z)+6z 9(z-1)=-3(3-z)+6z
Since z is on the right side of the equation, switch the sides so it is on the left side of the equation.
-3(3-z)+6z=9(z-1)
Simplify -3(3-z)+6z.
Simplify each term.
Apply the distributive property.
-3⋅3-3(-z)+6z=9(z-1)
Multiply -3 by 3.
-9-3(-z)+6z=9(z-1)
Multiply -1 by -3.
-9+3z+6z=9(z-1)
-9+3z+6z=9(z-1)
-9+9z=9(z-1)
-9+9z=9(z-1)
Simplify 9(z-1).
Apply the distributive property.
-9+9z=9z+9⋅-1
Multiply 9 by -1.
-9+9z=9z-9
-9+9z=9z-9
Move all terms containing z to the left side of the equation.
Subtract 9z from both sides of the equation.
-9+9z-9z=-9
Combine the opposite terms in -9+9z-9z.
Subtract 9z from 9z.
-9+0=-9
-9=-9
-9=-9
-9=-9
Since -9=-9, the equation will always be true for any value of z.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for z 9(z-1)=-3(3-z)+6z

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top